Dissecting aneurysms of the posterior cerebral artery – A retrospective review of imaging, angiographic characteristics, endovascular management and outcome. Issue 2 (April 2021) - Jabeen, Shumyla; Pendharkar, Hima S; Prasad, Chandrajit; HR, Arvinda; Saini, Jitender; Gupta, Arun Kumar; Shukla, Dhaval
Purpose: To review management, clinical and imaging outcomes of dissecting posterior cerebral artery (PCA) aneurysms with emphasis on endovascular management in the form of parent vessel occlusion (PVO) at a tertiary care center. Methods: Thirty-six dissecting PCA aneurysms (19 ruptured) encountered at our center between January 2013 and November 2019 were reviewed for aneurysm location/size/presence of fetal PCA/management. Postprocedural imaging of patients who underwent endovascular intervention was reviewed for PCA territory infarcts and clinical records assessed for presence of neuro-deficits and outcome. None of the patients underwent a balloon test occlusion (BTO) prior to PVO. Results: The location of the aneurysms was as follows-P1 = 8/P1-P2 = 11/P2 = 5/P2-P3 = 10/P3 = 2. The mean size was 11.7x6.8 mm. Endovascular intervention was carried out in 20 patients in the form of PVO with coiling in 16 patients, coiling alone in 3 patients, and reconstruction of the left PCA with flow diverter deployment in one patient. Postprocedural PCA territory infarct was seen in 5 cases of PVO out of which 4 had a good functional recovery. Overall, 15/16 patients (93.7%) who underwent PVO had mRS ≤ 2 on follow-up. The single case with flow diverter also developed an infarct and had adverse outcome on follow up. Conclusion: Among the various management strategies for dissecting PCA aneurysms, PVO is feasible and relatively safe even in absence of BTO in scenarios like critically ill patients with ruptured aneurysms, difficult access and financial constraints. Thromboembolic complications and antiplatelet therapy is a concern in reconstructive strategies.